2008
DOI: 10.2174/1874297100801010010
|View full text |Cite
|
Sign up to set email alerts
|

Human Enterovirus 71 Disease: Clinical Features, Epidemiology, Virology, and Management

Abstract: The purpose of this review was to summarize the epidemiology, clinical pictures, and virology of enterovirus 71 (EV71) infection. An epidemiological study in Taiwan revealed that the reported incidence of mild cases of hand-footmouth disease/herpangina (HFMD/HA) varied from year to year; seasonal variations in incidence were observed, with an incidence peak observed during the summer season. The study also showed that different enteroviruses co-circulate in the community, and seroepidemiological studies sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Outbreaks of enteroviral encephalitis in children have been reported from neighboring countries India1819 and China20. Since 1997, there have been reports of large outbreaks of EV71 associated hand, foot and mouth disease among children from the Asia pacific region2122. Although these outbreaks affected only children, we tested for EV71 in our patients but none were detected in our samples.…”
Section: Discussionmentioning
confidence: 65%
“…Outbreaks of enteroviral encephalitis in children have been reported from neighboring countries India1819 and China20. Since 1997, there have been reports of large outbreaks of EV71 associated hand, foot and mouth disease among children from the Asia pacific region2122. Although these outbreaks affected only children, we tested for EV71 in our patients but none were detected in our samples.…”
Section: Discussionmentioning
confidence: 65%
“…The study period was chosen because only immunofluorescence was used before 1995, and more recent samples were not included to avoid the bias of the exclusive bottle-feeding campaign for HTLV-1 carrier mothers that began in the late 1980s. 8 The seroprevalence of HTLV-1 was analyzed using binary logistic models respectively over five age bands of G [16][17][18][19] (16 ≤ age at donation < 20 years old), G 20-29 (20 ≤ < 30), G [30][31][32][33][34][35][36][37][38][39] (30 ≤ < 40), G [40][41][42][43][44][45][46][47][48][49] (40 ≤ < 50) and G 50-64 (50 ≤ < 65) with gender and study epochs (year at donation: 1995, 1996, 1997 and 1998) as independent variables. The age at donation was not included within the model because the seroprevalence in each age band within our study is not likely to reflect the natural age-related change because of potential biases (see Section 5 for detail).…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary evidence in male subjects compared with female subjects suggests a higher prevalence of orally/enterally acquired infections, such as enterovirus 71, 31,32 enteric adenovirus, 33,34 and rotavirus, 34 resulting in a higher incidence of diarrhoea 35 and hand, foot and mouth disease. 31,32 Several studies did not find these gender-specific differences. 36,37 Of special note, a study in Australia based on over 1800 blood samples demonstrated male dominant seropositivity of poliovirus in younger age groups; an opposite trend was seen in the adult age groups.…”
Section: Potential Mechanism Of Paradoxical Male Predominance Of Htlvmentioning
confidence: 98%